The role of droughts and religious cleavages in pastoralist conflict in Nigeria - Ruud Koopmans; Daniel Meierrieks; Daniel Tuki (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2026)
This article studies the role of environmental and religious factors in the occurrence of pastoralist conflict in Nigeria using panel data at the 0.5 x 0.5ê grid cell level between 1997 and 2020. The empirical analysis provides robust evidence that the occurrence of droughts does not raise the likelihood of pastoralist conflict in those parts of the country where Muslim herders face a largely Muslim sedentary population. However, when there is a potential for interreligious tensions (i.e., in predominantly Christian parts of Nigeria), droughts significantly fuel pastoralist violence. That is, the adverse interaction between droughts and religious cleavages creates particularly potent conditions for the emergence of pastoralist conflict. This interpretation is supported by original survey data collected in 2021, which shows that Christians and Muslims disagree about the participants and causes of pastoralist conflict in Nigeria, again emphasizing the role of religious divides in this conflict. – – Anhand von Paneldaten auf einem 0,5ê 0,5ê-Raster für die Jahre 1997-2020 untersucht dieser Artikel, welchen Einfluss Umweltfaktoren und Religion auf Konflikte um Weideland in Nigeria haben. Die empirische Analyse liefert robuste Befunde: In Landesteilen, in denen muslimische Viehhirten auf eine überwiegend muslimische sesshafte Bevölkerung treffen, erhöhen Dürren nicht die Wahrscheinlichkeit solcher Konflikte. In Regionen mit potenziellen interreligiösen Spannungen, das heißt in vorwiegend christlichen Teilen Nigerias, begünstigen Dürren hingegen signifikant die Gewalt. Mit anderen Worten schafft die ungünstige Wechselwirkung zwischen Dürren und religiöser Spaltung besonders explosive Bedingungen für das Entstehen von Konflikten um Weideland. Diese Deutung wird durch selbst erhobene Umfragedaten aus dem Jahr 2021 gestützt, die zeigen, dass Christen und Muslime unterschiedliche Auffassungen darüber haben, wer an solchen Konflikten beteiligt ist und welche Ursachen ihnen zugrunde liegen, was die Rolle religiöser Gegensätze in diesem Konflikt erneut betont.
Keywords: D74; Q54; 300; Konflikte um Weideland; Dürren; religiöse Gewalt; Nigeria; Fulani; Umfrageergebnisse; pastoralist conflict; droughts; religious violence; Nigeria; Fulani; survey evidence